THE ROLE OF ASSESSMENT LITERACY IN EFL - Sarvarova , Gulshan (Ижтимоий-гуманитар фанларнинг долзарб муаммолари / Актуальные проблемы социально-гуманитарных наук / Actual Problems of Humanities and Social Sciences., 2023)
Today, meeting educational needs is considered an important element of the development process. In particular, the "importance of assessment literacy" introduced in order to improve the quality of learning English as a foreign language plays a special role in teaching English. For this purpose, fundamental changes and reforms are taking place in the educational system of Uzbekistan today, one of which is the participation of our Republic in international evaluation studies. Primary education, as the most important part of education, needs to improve its quality. In particular, a high level of reading literacy is one of the most necessary factors at this stage of education. Although it has not been long since our country entered the education system, international evaluation programs are considered as an urgent issue today.